Uncovering the Endogenous Bacteria Involved in the Synthesis of Formaldehyde in Tiger Grouper Fish (Epinephelus fuscoguttaus) - Sufriadi, Elly; Helwati, Hira; Nurfahmi, Nurfahmi (Universitas Syiah Kuala, 2023)
This study aimed to isolate and identify specific bacteria responsible for the conversion of trimethylamine oxide (TMAO) into formaldehyde in tiger grouper (Epinephelus fuscoguttatus). The gastrointestinal tract of tiger grouper specimens was sampled, and bacterial colonies were isolated using nutrient agar (NA) and screened on TMAO media. Bacterial isolates capable of producing formaldehyde were identified. The implications of these findings extend to food safety, scientific research, medical diagnostics, and industrial applications. Further investigation is needed to elucidate the enzymatic pathways and genetic factors associated with formaldehyde production in these bacteria. Evaluation of the antibacterial compound production capability revealed inhibitory zones against Escherichia coli, indicating the potential for bactericidal properties. Gram staining and scanning electron microscopy (SEM) were employed to characterize the formaldehyde-producing bacteria, revealing their gram-positive nature and rod-shaped morphology. This study provides insights into the role of specific bacteria in formaldehyde production, paving the way for future research and applications in various fields.